2020
DOI: 10.2196/17842
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Delivery of the Diabetes Prevention Program in People With Prediabetes: Randomized Controlled Trial

Abstract: Background The Centers for Disease Control and Prevention (CDC) diabetes prevention program (DPP) has formed the foundation for Type 2 Diabetes Mellitus (T2DM) prevention efforts and lifestyle change modifications in multiple care settings. To our knowledge, no randomized controlled trial has verified the efficacy of a fully mobile version of CDC’s diabetes prevention program (DPP). Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(118 citation statements)
references
References 44 publications
6
112
0
Order By: Relevance
“…Schwalm et al 20 reported an intervention in which non-physician healthcare providers with the support of an algorithm-based app significantly reduced blood pressure and reported no adverse events from the use of the intervention. Finally, Toro-Ramos et al 21 found that a coach-guided mobile-delivery system reduced weight in pre-diabetic patients while reporting no adverse events from using the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwalm et al 20 reported an intervention in which non-physician healthcare providers with the support of an algorithm-based app significantly reduced blood pressure and reported no adverse events from the use of the intervention. Finally, Toro-Ramos et al 21 found that a coach-guided mobile-delivery system reduced weight in pre-diabetic patients while reporting no adverse events from using the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Quality assessment is presented in Supplementary Material 1.5 . Two of the included studies 20 , 21 were deemed well-conducted and had a low risk of bias. However, two other included studies 18 , 19 had a medium risk of bias due to limited information regarding sampling 18 and lack of sufficient information regarding the outcome measures.…”
Section: Resultsmentioning
confidence: 99%
“…Noom is a mobile health behavior change weight loss program that has demonstrated effects on clinically significant weight loss [ 37 , 38 ]. The Noom Healthy Weight program is based on Cognitive Behavioral Therapy (CBT), third-wave CBT, and motivational interviewing techniques, all of which aid in behavior change and weight control [ 39 , 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Noom is a mobile commercial behavior change program that has led to clinically significant short-term and long-term weight reduction [33,34]. After voluntarily signing up for the program, users receive a curriculum; logging features for food, weight, and exercise; a 1:1 coach; and an online group that provides social support led by a group coach.…”
Section: Program and Food Categorization Systemmentioning
confidence: 99%